A Comparative Study of Different Cases of Installation Art from Arabic artworks and global artworks - Rafee, Y.M; Salameh, M.A.B (Everant Publisher Pvt. Ltd., 2018)
This paper discusses the influence of the political situations on changing the idea in the material used in contemporary installation art in the Arab region. There was a change in the idea of the Arabic artworks which used the same material as in other global artworks but with a different idea. The study compared artworks (study sample) and global artworks that used the same material. The study sample contained two Arabic contemporary installation artworks from 2010 -2015 to confirm if political situations were the reason for this change in idea. The findings proved the influence of these political situations on changing the idea in Arabic contemporary installation art.